Analysis of Semantic Errors in students at the Mafaza Indonesia Islamic Boarding School - Marlina, Lina; Setia Budi, Firmansah (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aims to determine several linguistic phenomena in students at the Mafaza Indonesian Islamic Boarding School, including language errors at the semantic level, this is intended to find out the causes or problems behind the occurrence of these errors, then overcome them by analyzing and mentioning the correct form of each error. In addition, this study also aims to find some efforts that can be made to minimize the occurrence of errors such as increasing the language level of the students. The approach used in this study is a qualitative descriptive approach. The results of the study stated that: (1) There were errors at the semantic level among students at the Mafaza Indonesian Islamic Boarding School when they spoke Arabic. At least 70 language errors have been found at the semantic level, as it has also been found that the (main) cause of these errors is literal translation; (2) In an effort to correct language errors as well as minimize the occurrence of such errors, there are several things that need to be done by the teacher: First, conduct a small research on language errors in the place where he teaches. Second, get used to speaking Arabic properly and correctly, so that students can imitate and correct their own mistakes. If it is necessary to correct the students' mistakes, as much as possible the teacher does not say the word "WRONG" so as not to cause fear in the students to speak Arabic in the future. Third, as a preventive measure to avoid such mistakes, it is important for a teacher not to teach Arabic vocabulary without teaching how to use it, because that is the main reason that leads students to use and rely on literal translation.Keywords:Â Semantic Error Analysis, Literal Translation, Mafaza Indonesia Islamic Boarding School